EXAMINING ISLAMIC TEXTS ON THE SLOPE OF MOUNT KAWI, MALANG, EAST JAVA - Rohmah, Nurul Baiti; Awalin, Fatkur Rohman Nur; Rejo, Uman (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This research presents the philological study's findings on Islamic manuscripts discovered on the slopes of Kawi Mountain in Malang, East Java. The study employs a manuscript research method focusing on codicological aspects and the diplomatic method to preserve authenticity. Eight Islamic manuscripts were categorized into originals with identifiable titles, manuscripts without titles, and hand-copied versions by Anut Ekowiyono. These manuscripts are written in the new Javanese language, utilizing various krama-ngoko styles and the Arabic Pegon script. Inadequate philological treatment resulted in damage to Anut Ekowiyono's collection. After codicological examination, the texts were accurately identified, showing differences from their previous state. The research suggests the likelihood of more undiscovered Islamic manuscripts in the area. The study sheds light on the linguistic and historical importance of these Islamic texts, emphasizing the need for preservation and further exploration of undiscovered manuscripts in the region.